2005
DOI: 10.1055/s-2005-870329
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy Structured Terminology (CEST): Proposal of a Standardized and Structured Terminology for Reporting Capsule Endoscopy Procedures

Abstract: This Capsule Endoscopy Structured Terminology (CEST) is a copy− righted work, protected by United States and worldwide copy− right laws and treaties. Users of the CEST are hereby granted a free license to use, copy or distribute the CEST in connection with supporting a structured terminology for capsule endoscopy, subject to the following conditions: 1. This copyright and terms of use notice must be displayed on each and every copy of the CEST, on all manuals and other mate− rials used in connection with the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 0 publications
1
95
1
5
Order By: Relevance
“…Las contraindicaciones del examen están constituidas por todas aquellas circunstancias que impidan el libre tránsito de la CE por el tubo digestivo (estenosis, obstrucción intestinal, etc) 2 . Su seguridad en el embarazo aún no ha sido establecida Los hallazgos fueron definidos según la terminología endoscópica estandarizada [26][27][28] , y se clasificaron como "positivos" (explican con claridad el cuadro clínico), "sospechosos" (podrían o no explicar el cuadro clínico) y "negativos" (normal) según lo establecido por Penazzio et al 29 …”
Section: Materials Y Métodounclassified
“…Las contraindicaciones del examen están constituidas por todas aquellas circunstancias que impidan el libre tránsito de la CE por el tubo digestivo (estenosis, obstrucción intestinal, etc) 2 . Su seguridad en el embarazo aún no ha sido establecida Los hallazgos fueron definidos según la terminología endoscópica estandarizada [26][27][28] , y se clasificaron como "positivos" (explican con claridad el cuadro clínico), "sospechosos" (podrían o no explicar el cuadro clínico) y "negativos" (normal) según lo establecido por Penazzio et al 29 …”
Section: Materials Y Métodounclassified
“…Small-bowel lesions were defined as so-called ''typical ulcerations'' corresponding to excavated lesions (erosions and ulcers) described in the CE structured terminology. 9 Mow et al 13 described ulcers as white lesions within a crater and with surrounding erythema, whereas superficial white lesions with surrounding erythema were characterized as erosions. The definitive diagnosis of UC was based on a surgical specimen with diffuse involvement starting distally and with an absence of transmural inflammation.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The digital video image streams of the examinations were downloaded into the RAPID system. The images were then visualized by 2 observers, using the CE structured terminology 9 and were described according to the following classification.…”
Section: Ce Proceduresmentioning
confidence: 99%
“…The study by Maiden et al [10] was interesting, as it showed that significant lesions can occur even after a short course of NSAID treatment in healthy individuals. However, the study had several methodological limitations: (1) The interpretation of CE images was often difficult [11] and the clinical relevance of lesions detected by CE was not always established, since such lesions could be found in the absence of any treatment in healthy individuals [12] . (2) Other causes of intestinal lesions such as chronic ischemia were not excluded.…”
Section: Description Of the Lesionsmentioning
confidence: 99%
“…(2) Other causes of intestinal lesions such as chronic ischemia were not excluded. (3) A standardized terminology allowing a consistent description of the lesions and comparisons between different studies was lacking [11] . Moreover, DBE provides a direct access to intestinal lesions detected by CE and biopsy specimens can be obtained.…”
Section: Description Of the Lesionsmentioning
confidence: 99%